2002
DOI: 10.1095/biolreprod66.3.796
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Wild European Mouflon: The First Example of Genetic Management Using a Complete Program of Reproductive Biotechnologies

Abstract: Although the potential use of reproductive biotechnologies for safeguarding endangered wildlife species is undoubted, practical efforts have met with limited success to date. In those instances in which modern technologies have been adapted to rescuing rare or endangered species, procedures have been applied piecemeal, and no consistent breeding program based on reproductive biotechnologies has been undertaken. Here we describe for the first time the rescue of an endangered species, the European mouflon (Ovis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…This is in agreement with the results of this study, as the percentage of abnormal spermatozoa found was relatively low. This would facilitate the creation of germplasm banks of not only endangered species (Ptak et al 2002, Kozdrowski et al 2011) but also those that could be at risk in the future (Holt and Pickard 1999). In addition, epididymal spermatozoa collected postmortem could be used for artificial insemination (Garde et al 2006, Morrow et al 2009), in vitro fertilization (Garcia-Alvarez et al 2009) and in vitro embryo production (Comizzoli et al 2001, Martins et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the results of this study, as the percentage of abnormal spermatozoa found was relatively low. This would facilitate the creation of germplasm banks of not only endangered species (Ptak et al 2002, Kozdrowski et al 2011) but also those that could be at risk in the future (Holt and Pickard 1999). In addition, epididymal spermatozoa collected postmortem could be used for artificial insemination (Garde et al 2006, Morrow et al 2009), in vitro fertilization (Garcia-Alvarez et al 2009) and in vitro embryo production (Comizzoli et al 2001, Martins et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in Japanese quail Coturnix japonica, Wingfield et al [47] suggested the use of gonadotropins to induce gonadal maturation in non-reproductive individuals to bring them into reproductive condition before old, reproductively experienced individuals died out. Although these techniques are still being developed, the results look promising [48]. Similarly, physiological assessments of gonadal and endocrine state in endangered Hawaiian honey creepers Trepanididae spp.…”
Section: Box 1 Physiological Assessment Of Environmental Stressorsmentioning
confidence: 99%
“…These populations derive from Corsican and Sardinian mouflons, which live on the islands in small and isolated groups. To maintain resources of the pure breed, it is very important to study and preserve the natural populations of Corsican and Sardinian mouflons (Ptak et al 2002), also considered ancestors of the modern sheep breeds (Naitana et al 1990;Hiendleder et al 1998).…”
Section: Introductionmentioning
confidence: 99%